PENDETEKSI KEBOCORAN TABUNG LPG MELALUI SMS GATEWAY MENGGUNAKAN SENSOR MQ-6 BERBASIS ARDUINO PADA PT BANGUN INTI GEMILANG - Moch. Ibnu Safari; Listina Nadhia Ningsih; Muhammad Husni Farid (UNIVERSITAS RAHARJA, 2016)
The increasing level of population, making the level of consumption on natural resources is also increasing. In the case of this increase occurred in the use of fuels LPG (Liquefied Petroleum Gas). With the LPG fuel is increasing, allowing the occurrence of fires caused by leakage of LPG gas. However, not all providers of LPG gas cylinders provide additional safety systems on LPG they sell. So it takes a LPG gas leak detectors and systems that can perform countermeasures in case of leakage of LPG cylinders. For that made the tool pendekteksi leakage of LPG gas by using a system of notification SMS by using SIM900a, Sensor MQ-6 that can detect gas LPG and DC motor to drive the exhaust to neutralize the air when leakage of LPG gas, so as to provide a warning if the owner of LPG cylinders being are outside the house. All the components are controlled using Arduino Uno. This tool has the advantage of being easy to use and compatible with all communication devices based on SMS. And this tool can be developed using the Internet-based notfikasi.